Marketing management in Turkey - Ozturkcan, Selcen; Yolbulan Okan, Elif (Marketing in emerging markets, 2018)
Emerging market economies have long been a significant driver of global growth, and ever since the beginning of the new millennium, they have gained greater importance than ever. Economists state that the economies of emerging countries are rapidly catching up with the those of developed countries and are even predicted to overtake some of them by 2020. A deep understanding of emerging markets is crucial, then, in order to build tailored products and marketing programs that will capitalize on such rapid growth. In "Marketing Management in Turkey", Elif Yolbulan Okan and Selcen Ozturkcan examine marketing opportunities, market potential, and standardization and customization opportunities available within one of the fastest growing of these emerging economiesnamely, the Turkish economy, which according to a recent PWC report could outstrip the Italian economy by 2030 in many areas. Along the way, this book offers important insights into issues affecting all emerging markets, including common perceptions and misconceptions around the opportunities they offer. "Marketing Management in Turkey" will be of keen interest to practitioners interested in investing in emerging markets, and it will also have much to offer to researchers and students interested in the future of the global economy.